Relocation to Representation: The Changing Face of Minneapolis City Politics. - Lillehaug, Kara M. (Tufts Archival Research Center, 2014)
Abstract: In 2013, Abdi Warsame was elected to Minneapolis City Council, becoming the highest ranking Somali in the United States and usurping three-time incumbent Robert Lilligren. His election came on the heels of a transformation of the redistricting process in the City of Minneapolis and an endorsement from the largest party in Minneapolis, the Democratic Farmer Labor Party (DFL). This thesis is divided into two parts. The first section reveals and explores the systems of power constructed by white, male,heterosexual interests that are present and operating in Minneapolis city politics. Specifically, I focus on how the influence of powerful special interests in Warsame's election and the lack of multicultural literacy in the Minneapolis DFL almost cost Warsame the DFL endorsement and have potentially altered his decisions after election within City Hall. The second section is focused on how the Somali community, as led by Warsame, was able to overcome these structures of power through their use of innovative grassroots organizing methods. In particular, I center on the new application of the Get Out The Vote method and reliance on alternative media outlets. As such, Warsame's story, although unique, illuminates some of the invisible structures of power present in many cities politics that operate, exclude, and manipulate newcomers and marginalized communities while providing strategies and methods for other disenfranchised communities seeking political power to overcome these barriers in their own communities.